Utilisation and influence of condiments prepared from fermented legumes on quality profile of meat (2014)
This study was conducted to investigate the utilization and influence of condiments prepared from four fermented legumes; African locust-bean (Parkia biglobosa), melon seeds (Citrullus vulgaris), soybean (Glycine max) and cotton seeds (Malvaceae gossypium). They were processed, dried, milled and 25% solution of each condiment was made using purified water. 200 g fresh beef from the thigh cut of White Fulani bull (Bos indicus) was purchased, divided into 4 parts of 50 g and 20 ml of condiments solution was injected into each beef with a syringe and needle each condiment and 50 g beef constituted a treatment thus; TO = control (No condiment), TI = Beef steak + locust bean condiment, T2 = Beef + melon seeds condiment, T3 = Beef + soybean condiment, T4 = Beef + cotton seeds condiment. The injected beef steaks were wrapped in foil paper and broiled in oven at 170ºC for 20 mins. Data were collected on physicochemical, microbiological and sensory properties of processed beef and were subjected to analysis of variance (ANOVA) at p = 0.05 in a completely randomized design experiment. The results showed that cooking loss and shear force were lower in TI, while water holding capacity (WHC) and yield were higher. Protein and ash were high in TI followed by T3 while fat and fibre were significantly lower. Aerobic and anaerobic bacteria were significantly the same across the treatments while coliform and fungal counts were lower except in T2 and T4. Treatment1 was adjudged higher in all the eating qualities except colour and was well accepted. It is therefore, recommended that locust bean condiment be used in processing meat followed by soybean condiment. However, further investigation should be carried out on varied levels of locust bean condiment to determine the level that will give better colour which can improve the meat product acceptability and consumption.